Counselling needs of adolescents in certain South African sub-cultures - Juggath, A Kishore (My University, 2015)
This study attempted to survey adolescent needs and concerns. It also tried to discover whether teenagers ln high schools accept the idea of counsellors in their schools, in this study three private schools, representing Jewish, English and "non-white" subcultures in Johannesburg were chosen for the survey. Samples of standard seven and standard nine pupils completed a checklist indicating their concerns and their willingness to discuss these concerns with others.